Evidence for non-exponential elastic proton–proton differential cross-section at low |t| and s=8TeV by TOTEM - G. Antchev; P. Aspell; I. Atanassov; V. Avati; J. Baechler; V. Berardi; M. Berretti; E. Bossini; U. Bottigli; M. Bozzo; P. Broulím; A. Buzzo; et al. (Nuclear Physics B, 2015)
The TOTEM experiment has made a precise measurement of the elastic proton–proton differential cross-section at the centre-of-mass energy s=8 TeV based on a high-statistics data sample obtained with the β⁎=90 m optics. Both the statistical and systematic uncertainties remain below 1%, except for the t-independent contribution from the overall normalisation. This unprecedented precision allows to exclude a purely exponential differential cross-section in the range of four-momentum transfer squared 0.027<|t|<0.2 GeV2 with a significance greater than 7 σ. Two extended parametrisations, with quadratic and cubic polynomials in the exponent, are shown to be well compatible with the data. Using them for the differential cross-section extrapolation to t=0, and further applying the optical theorem, yields total cross-section estimates of (101.5±2.1) mb and (101.9±2.1) mb, respectively, in agreement with previous TOTEM measurements.